Characteristics and evaluation of acute exacerbations in chronic interstitial lung diseases. (July 2021) - Kershaw, Corey D.; Batra, Kiran; Torrealba, Jose R.; Terada, Lance S.
Abstract: Acute exacerbations of fibrosing interstitial lung disease (ILD) occur in both idiopathic pulmonary fibrosis (IPF) as well as non-IPF ILDs. An expert consensus definition has allowed for more frequent reporting of IPF exacerbations. The same is lacking for non-IPF ILD exacerbations. The incidence of non-IPF ILD exacerbations is likely less than in IPF, but the two entities share similar risk factors, such as increased frequency as physiologic derangements advance. The radiologic and histopathologic spectrum of acute ILD exacerbations extends from organizing pneumonia (OP) to the more treatment-refractory diffuse alveolar damage (DAD) pattern. Indeed, responsiveness to various therapies may depend on the relative components of these entities, favoring OP over DAD. There are no proven therapies for acute ILD exacerbations. Corticosteroids are a mainstay in any regimen although clear evidence of benefit does not exist. A variety of immunosuppressant agents have purported success in historical cohort studies – cyclophosphamide, cyclosporine A, and tacrolimus most commonly. Only one randomized controlled trial has been published, studying recombinant thrombomodulin for IPF exacerbation, but the primary outcome of survivor proportion at 90 days was not met. Other novel therapies for ILD exacerbations are still under investigation. The short and long-term prognosis of acute exacerbations of ILD is poor, especially in patients with IPF. Transplant referral should be considered early for both IPF as well as fibrosing non-IPF ILDs, given the unpredictability of the exacerbation event. Highlights: Exacerbations of IPF and non-IPF ILDs are a devastating complication with significant morbidity and mortality. Exacerbations of non-IPF ILDs are less reported and studied than exacerbations of IPF. Incidence of ILD exacerbations increases as disease progresses. Histopathology of exacerbations occurs along a spectrum of manifestations that often overlap and/or occur simultaneously. Response to treatment favors organizing pneumonia over diffuse alveolar damage during the exacerbation episode.